Comment usait-on du vrai et du faux dans les appellations des articles de Paris ? Le cas des bijoux en jais et des peignes du Pays d’Olmes - Bruno Evans (Les Cahiers de Framespa)
Many “articles de Paris” had only the name of Paris; this was the case of part of the jet jewellery and combs made in “pays d’Olmes”, 800 kilometres south of the capital. No buyer could have any guarantee either of the Paris origin of these articles or of their authenticity. Indeed, for people of the period, the quality of the products was not defined so much by the genuineness of raw material as by its quality. Since the 18th century, there have been imitations of jet jewellery so hard to distinguish that black glass is now called French jet. Due to the scarcity of boxwood, manufacturers have also produced imitations by painting wood. Then, to move their products upmarket, they designated as Ireland and buffalo the white and black horns coming from Latin America while stamping many of their combs as “Paris”. Finally, the image of the territory probably suffered from its strategies of use of the fake.